A vanadium/aspirin complex controlled release using a poly(ß-propiolactone) film : Effects on osteosarcoma cells - Cortizo, María Susana (2001)
A delivery system for vanadium was developed using poly(ß-propiolactone)(PßPL) films. The release kinetics of a complex of vanadium (IV) with aspirin (VOAspi) was evaluated with lms prepared from polymers of different molecular weights, as well as with variable drug load. A sustained release of vanadium over 7 days was achieved. The drug release kinetics depends on contributions from two factors: (a) diffusion of the drug; and (b) erosion of the PßPL lm. The experimental data at an early stage of release were tted with a diffusion model, which allowed determination of the diffusion coef cient of the drug. VOAspi does not show strong interaction with the polymer, as demonstrated by the low apparent partition coef cient (approximately 10-2). UMR106 osteosarcoma cells were used as a model to evaluate the anticarcinogenic effects of the VOAspi released from the PßPL lm. VOAspi–PßPL lm inhibited cell proliferation in a dose-response manner and induced formation of approximately half of the thiobarbituric acid reactive substances (TBARS), an index of lipid peroxidation, compared to that with free VOAspi in solution. The unloaded PßPL lm did not generate cytotoxicity, as evaluated by cell growth and TBARS. Thus, the polymer-embedded VOAspi retained the antiproliferative effects showing lower cytotoxicity than the free drug. Results with VOAspi–PßPL lms suggest that this delivery system may have promising biomedical and therapeutic applications.